1986
DOI: 10.1007/bf00470614
|View full text |Cite
|
Sign up to set email alerts
|

Calcium antagonists in the treatment of sudden deafness

Abstract: In the treatment of patients with sudden deafness, we found no significant difference between an oral calcium antagonist (nifedipine) and intravenous naftidrofuryl given concomitantly with vitamin A, vitamin E, and zinc. This prospective randomized study in 50 patients again shows that recovery to useful hearing levels tends to be spontaneous and independent of the type of medical treatment given. Irrespective of their capability to prevent contractions of cerebral vascular smooth muscle induced by neurotransm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 5 publications
0
13
1
2
Order By: Relevance
“…Hydroxyethyl starch carrier solution reduces the hematocrit level and platelet aggregation. 187,188 These therapies have considerable side effects. Different types of treatment entail different risks.…”
Section: Supporting Textmentioning
confidence: 99%
“…Hydroxyethyl starch carrier solution reduces the hematocrit level and platelet aggregation. 187,188 These therapies have considerable side effects. Different types of treatment entail different risks.…”
Section: Supporting Textmentioning
confidence: 99%
“…It is suggested that vasodilators promote cochlear blood flow, reverse presumed vasospasm and increase local oxygenation, but no double-blind randomized clinical work with a vasodilator versus placebo has been performed. Procaine or a calcium antagonist (nifedipine) seems unable to enhance hearing recovery [38,39]. Some studies have suggested that carbogen inhalation (mixture of 5% CO 2 and 95% O 2 ) increases the perilymphatic oxygenation of about 10 mm Hg [40].…”
Section: Which Benefit Can Be Expected From Therapy ?mentioning
confidence: 99%
“…The first trial to treat sudden hearing loss with the calcium channel blocker nimodipine was re ported in 1980, but two subsequent studies have failed to show a positive influence on hearing loss when utilizing calcium antagonist drugs [24][25][26], Histopathologic devel opment of noise trauma and sudden hearing loss are com bined with metabolic damage to the cells of the cochlea, including an intracellular calcium overload [27], Myocar dial cells are known to be less sensitive to ischemic insult in the presence of a sufficient concentration of calcium channel blockers, preventing an elevated calcium influx during reperfusion. The same is possibly true for the hair cells of the cochlea.…”
Section: Discussionmentioning
confidence: 99%